Validation of a multipolar pulsed field ablation catheter for endpoint assessment in pulmonary vein isolation procedures. (19th May 2022) - Kueffer, T; Baldinger, SH; Servatius, H; Madaffari, A; Seiler, J; Muehl, A; Franzeck, F; Thalmann, G; Asatryan, B; Haeberlin, A; Noti, F; Tanner, H; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): FP7/2007-2013, №602299, EU-CERT-ICD Objective: To validate the performance of a multipolar PFA catheter compared to a standard pentaspline 3D-mapping catheter for endpoint assessment of PVI. Background: Pulsed field ablation (PFA) for pulmonary vein isolation (PVI) using single-shot devices combines the benefits of high procedural efficacy and safety. A newly available multipolar PFA catheter allows real-time recording of pulmonary vein (PV) signals during PVI. Methods: Patients undergoing first PVI using PFA with the standard ablation protocol (8 applications per PV) were studied. Entrance- and exit-block (10V/2ms) were assessed using the PFA catheter. Subsequently, a high-density bipolar voltage 3D electro-anatomical map (3D-EAM) was constructed using a standard pentaspline 3D-mapping catheter. Additional PFA applications were delivered only after confirmation of residual PV-connection by 3D-EAM. Results: In 56 patients, 213 PVs were targeted for ablation. Acute PVI was achieved in 100% of PVs: in 199/213 (93%) PVs with the standard ablation protocol alone and in the remaining 14 PVs after additional PFA applications. Accuracy of PV assessment with the PFA catheter after the standard ablation protocol was 91% (194/213 veins). In 5/213 (2.3%) PVs, the PFA catheter incorrectly indicated PV-isolation. In 14/213 (6.6%) the PFA catheter incorrectly indicated residual PV-conduction due to high-output pace-capture. When the output was reduced to 5V/1ms, pace-capture was reduced to 0.9% (2/213). Conclusion: A novel multipolar PFA catheter allows reliable endpoint assessment for PVI. Due to its design, far-field sensing and high-output pace-capture can occur, which may require adjustment of standard pacing outputs for verification of exit-block.